A new Student Centre and the pedestrianization of the University of the Free State campus - Joubert, Ora (Acta Structilia, 2009)
Regrettably, academic buildings in South Africa often suffer from a Rstigma of ideological nepotism - a social phenomenon that is seldom conducive to architectural excellence. The University of the Free State in Bloemfontein is no exception, and consequently any new design commission is followed with both interest and envy.